Study of content and bioconcentration of heavy metal (Pb,Hg, and Cd) in green mussels (Perna viridis) based on different sizes and ages - Bella Krismonita; Indra Gumay Yudha; Munti Sarida; Qadar Hasani; Endang Linirin Widiastuti (Faculty of Marine and Fisheries, Universitas Syiah Kuala, 2023)
Green mussel (Perna viridis) has filter-feeding habits and a sessile way of life, with the main food components of plankton and organic matter in the waters. These food components can contaminate green mussels when it accumulates heavy metals. Therefore, this study aims to evaluate heavy metals content and the bioconcentration of lead (Pb), mercury (Hg), and cadmium (Cd) in green mussels based on different sizes and ages. The study was conducted on Pasaran Island, Lampung, Indonesia, and used green mussels aged 3, 5, 7 to 9 months as samples, with 2 replications. The AAS (Atomic Absorption Spectrophotometry) method was used in the analysis of Pb, Hg, and Cd, sampling technique used purposive sampling. The result showed that green mussels at different ages and sizes has impact on Pb content, while an increase of one unit of age and size of green mussels has no effect on the metal content of Hg and Cd. Furthermore, the highest bioconcentration of Pb and Hg was obtained at 9 months, while Cd was observed at 3 months. Based on the results of this study it can be concluded that the simple linear regression appropriate a functional relationship between Pb and the different ages and sizes green mussels cultivated on Pasaran Island , while heavy metals Hg and Cd appropriate with a polynomial quadratic approach and almost do not exist in the form of a functional relationship between Hg and Cd with the different ages and sizes green mussels. Even though it contains heavy metals in below the maximum limit, but care needs to be taken in addressing this phenomenon due to its nature heavy metals that can accumulate in living tissue, thus consuming green mussels containing heavy metals even in relatively small amounts is not recommended.Keywords:Filter feederSessileAccumulateOrganic matterContaminate